2007
DOI: 10.1176/appi.ajp.2007.06122032
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized Caudate Metabolic Abnormalities in Adolescent Major Depressive Disorder: A Proton MR Spectroscopy Study

Abstract: Objective-Proton magnetic resonance spectroscopy ( 1 H-MRS) has been increasingly used to examine striatal neurochemistry in adult major depressive disorder. This study extends the use of this modality to pediatric major depression to test the hypothesis that adolescents with major depression have elevated concentrations of striatal choline and creatine and lower concentrations of N-acetylaspartate.Method-Fourteen adolescents (ages 12-19 years, eight female) who had major depressive disorder for at least 8 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 65 publications
6
39
1
1
Order By: Relevance
“…This is consistent with previous research that showed that motor predominance does not affect depression or other non-motor symptoms 21. Mixed results on the lateralisation of depressive symptoms are also evident in non-PD samples, with some studies showing right-lateralised dysfunction,22 while others showed left-lateralised dysfunction 23. More research is therefore warranted on the lateralisation of depressive symptoms in both PD and non-PD samples.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with previous research that showed that motor predominance does not affect depression or other non-motor symptoms 21. Mixed results on the lateralisation of depressive symptoms are also evident in non-PD samples, with some studies showing right-lateralised dysfunction,22 while others showed left-lateralised dysfunction 23. More research is therefore warranted on the lateralisation of depressive symptoms in both PD and non-PD samples.…”
Section: Discussionsupporting
confidence: 90%
“…14,47,48 In an earlier report, our laboratory demonstrated smaller MT ratios in the caudate nucleus bilaterally in patients with type 2 diabetes and depression when compared with both healthy and diabetic controls. 46 In a magnetic resonance spectroscopy study, Ajilore et al 47 reported lower Glx, a glutamate/glutamine composite measure, in the subcortical regions bilaterally, in a voxel that included the head of the caudate, in patients with diabetes and depression when compared with controls.…”
Section: Discussionmentioning
confidence: 78%
“…Alterations in energy metabolism produced by animal models of depression, which are based on stress, correspond with impairments in the creatine-phosphocreatine pathway in severely depressed humans. In particular, imaging studies report decreased total creatine in the ACC (Mirza et al, 2006), left caudate (Gabbay et al, 2007), and medial prefrontal cortex (Venkatraman et al, 2009) in depressed patients. More severe episodes of depression have been associated with reduced total creatine in the frontal lobe (Kato et al, 1992) and the left dorsolateral prefrontal cortex (Michael et al, 2003).…”
Section: Discussionmentioning
confidence: 99%